Identification of circRNA/miRNA/mRNA regulatory network involving (+)-catechin ameliorates diabetic nephropathy mice - Chao Chen; Dina Zhu; Shuai Zhang; Wensheng Zhang (Food Science and Human Wellness)
(+)-Catechin (CE) is mainly found in green and black tea and has many biological effects, such as anti-inflammatory, anti-cancer, anti-viral effects, protecting human organs, especially the kidney. This study aims to identify the circRNAs induced by CE in db/db mice and their roles in diabetic nephropathy progression. After the db/db mice were treated with CE, RNA-seq was performed to identify the differentially expressed circRNA and mRNAs. The ceRNA regulatory network was constructed and analyzed using bioinformatics software and public databases (Cytoscape, ClueGO, MiRWalk, STRING, et al.). Our results revealed that 6 differentially expressed circRNAs are most associated with the cholinergic synapse, neurotrophin signaling pathway, and insulin signaling pathway. Among these, circRNA.5549 and circRNA.4712 might regulate Cd36, Cyp26b1, C8a, Cyp2j13, Grem2 genes through ceRNA regulatory mechanism in the presence of CE treatment. The expanded network of proteins interacting with these 5 genes shows that the TGF-β signaling pathway, signaling pathways regulating pluripotency of stem cell, fat digestion and absorption, and PPAR signaling pathway was highly enriched. Overall, circRNA.5549 and circRNA.4712 exhibit a promotive function in CE-treated db/db mice, especially in circRNA.5549/miR-29a-5P/Cd36 regulatory network, and this evidence suggest that their ceRNA regulatory network might be a therapeutic target for DN in humans.